Relationship between public procurement governance and the performance of government agencies in Indonesia - Fadlila, Alise Kurniarini (International Journal Labs, 2024)
The Government Goods/Services Procurement Policy Institute (LKPP) established a policy for measuring the procurement governance index (ITKP) for Government Agencies in Indonesia as one of the tools to achieve a